Agreement between Fitbit and ActiGraph Estimates of Physical Activity in Young Children. Issue 2 (3rd April 2023) - Schmidt, Michael D; Rathbun, Stephen L.; Chu, Zhixuan; Boudreaux, Benjamin D.; Hahn, Lindsay; Novotny, Eric; Johnsen, Kyle; Ahn, Sun Joo (Grace)
ABSTRACT: Physical activity (PA) estimates from the Fitbit Flex 2 were compared to those from the ActiGraph GT9X Link in 123 elementary school children. Steps and intensity-specific estimates of PA and 3-month PA change were calculated using two different ActiGraph cut-points (Evenson and Romanzini). Fitbit estimates were 35% higher for steps compared to the ActiGraph. Fitbit and ActiGraph intensity-specific estimates were closest for sedentary and light PA, while estimates of moderate and vigorous PA varied substantially depending upon the ActiGraph cut-points used. Spearman correlations between device estimates were higher for steps ( rs   = .70) than for moderate ( rs   =.54 to .55) or vigorous ( rs  =.29 to .48) PA. There was low concordance between devices in assessing PA changes over time. Agreement between Fitbit Flex 2 and ActiGraph estimates may depend upon the cut-points used to classify PA intensity. However, there is fair to good agreement between devices in ranking children's steps and MVPA.